Differences in bone quality and strength between Asian and Caucasian young men. Issue 2 (February 2017) - Kepley, A.; Nishiyama, K.; Zhou, B.; Wang, J.; Zhang, C.; McMahon, D.; Foley, K.; Walker, M.; Edward Guo, X.; Shane, E.; Nickolas, T.
Abstract Summary This is a cross-sectional study to assess differences in bone quality in young Asian and Caucasian (n = 30/group) men between 25 and 35 years. We found that Asians had smaller bones, thicker and denser cortices, and more plate-like trabeculae, but stiffness did not differ between groups. Introduction We conducted a cross-sectional study to assess differences in bone quality in young Asian and Caucasian (n = 30/group) men between 25 and 35 years. Methods We measured bone mineral density (BMD) at the spine, total hip (TH), femoral neck (FN), and forearm by dual energy X-ray absorptiometry (DXA), and bone geometry, density, microarchitecture, and mechanical competence at the radius and tibia by high-resolution peripheral quantitative computed tomography (HR-pQCT) with application of individual trabecula segmentation (ITS) and trabecular and whole bone finite element analysis (FEA). We measured load-to-strength ratio to account for differences in bone size and height, respectively. We used Wilcoxon rank sum and generalized linear models adjusted for height, weight, and their interaction for comparisons. Results Asians were 3.9 % shorter and weighed 6.5 % less than Caucasians. In adjusted models: by DXA, there were no significant race-based differences in areal BMD; by HR-pQCT, at the radius, Asians had smaller total and trabecular area (p = 0.003 for both), and denser (p = 0.01) and thicker (p = 0.04) cortices at the radius; by ITS, at the radius Asians, had more plate-like than rod-like trabeculae (PR ratiop = 0.01), greater plate trabecular surface (p = 0.009) and longer rod length (p = 0.002). There were no significant race-based differences in FEA or the load-to-strength ratio. Conclusions Asians had smaller bones, thicker and denser cortices, and more plate-like trabeculae, but biomechanical estimates of bone strength did not differ between groups. Studies are needed to determine whether these differences persist later in life.